Gaya Kepemimpinan Terhadap Kepuasan Kerja Dalam Novel Resign Karya Almira Bastari - Wahyu Ragil Putra Pamungkas; Dimas Anwar Choliq; Eva Dwi Kurniawan (Jurnal Ekonomi dan Bisnis Digital, 2022)
This research aims to find out and prove the influence of leadership style on job satisfaction in the novel Resign by Almira Bastari. The method used in this research is a qualitative method with text data collection techniques based on the novel Resign by Almira Bastari. The result of this research is that the applied leadership style affects employee job satisfaction